Fucoidan-loaded electrospun Polyvinyl-alcohol/Chitosan nanofibers with enhanced antibacterial activity for skin tissue engineering - ULAĞ, SONGÜL (My University, 2023)
The polymeric nanofiber may interact and control certain regeneration processes at the molecular level to repair damaged tissues. This research focuses on the development of characterization and antibacterial capabilities of polyvinyl alcohol (PVA)/chitosan (CS) nanofibres containing fucoidan (FUC) for tissue engineering as a skin tissue substitute. A control group consisting of 13% PVA/(0.1)% CS nanofiber was prepared. To confer antibacterial properties to the nanofiber, 10, 20, and 30 mg of FUC were incorporated into this control group. The scanning electron microscope (SEM) proved the homogeneous and beadless structures of the nanofibers. The antibacterial activity of the 13% PVA/(0.1)% CS/(10, 20, 30) FUC was tested against the S.aureus and E.coli and the results showed that with FUC addition, the antibacterial activities of the nanofibers increased. The biocompatibility test was performed with a fibroblast cell line for 1, 3, and 7 days of incubation and the results demonstrated that FUC addition enhanced the bioactivity of the 13% PVA/(0.1)% CS nanofibers. In addition, the biocompatibility results showed that 13% PVA/(0.1)% CS/10 FUC had the highest viability value for all incubation periods compared to the others. In addition, the tensile test results showed that; the maximum tensile strength value was observed for 13% PVA/(0.1)% CS/10 FUC nanofibers.
Keywords: Fucoidan; Chitosan; Electrospun; Nanofibers; PVA; Skin tissue engineering